Numerical simulation of direct contact condensation of subsonic steam injected in a water pool using VOF method and LES turbulence model. (January 2015) - Li, S.Q.; Wang, P.; Lu, T.
Abstract: The direct-contact condensation (DCC) of subsonic steam injected into a subcooled water pool has been simulated using the Volume of Fluid (VOF) multiphase flow model and Large Eddy Simulation (LES) turbulent flow model of FLUENT. A thermal equilibrium model has been introduced to simulate the phenomenon of DCC. The condensation model is a two resistance model which takes care of the heat transfer process on both sides of the interface. The numerical results for the steam plume can be divided into four stages: the initial stage, the maximum stability stage, the oscillatory stage and the detachment stage. Fairly good qualitative agreement was obtained with the available experimental data for the plume shape and evolution characteristics of the steam plume. In addition, it was found that the centerline axial temperature increases with the decrease of the centerline axial velocity at the pipe exit and the pressure oscillation is mainly affected by the steam velocity, steam condensation and subcooled water hydrostatic pressure. Highlights: A model was employed to model the phenomena of direct contact condensation. The numerical results are in good agreement with the data of Chan and Lee. The VOF method and LES turbulence model could be used to model the phenomena of DCC.